A comprehensive review on performance improvement of micro energy mechanical system: Heat transfer, micro combustion and energy conversion. (15th January 2022) - E, Jiaqiang; Luo, Bo; Han, Dandan; Chen, Jingwei; Liao, Gaoliang; Zhang, Feng; Ding, Jiangjun
Abstract: In order to strengthen the internal flow and heat transfer and increase the stability of the flame, various methods to improve combustion efficiency were proposed. In terms of spatial structure, the optimization methods are divided into two categories: insertion geometry and internal molding. Both of them change the combustion efficiency by affecting the flow and heat transfer, but the degree is different; for catalytic combustion, heat and mass transfer, heterogeneous/homogeneous reaction and other derivative processes are the key to improve the combustion efficiency; as for fuels, changing the type and mixing mode are effective means to improve combustion efficiency. In addition, the research on improvement of the energy conversion and emission performance of micro thermophotovoltaic(MTPV) system, micro thermoelectric(MTE) system and micro engine(ME) was reviewed. Compared with the existing research, it is found that the single optimization method has limitations, it cannot guarantee the positive effect under all operating conditions, the future research direction is to combine the advantages of a variety of optimization methods, besides, with the development and maturity of technology, the number of studies on diffusion combustion is increasing, and its practicability has been improved. Meanwhile, the further research and development of micro-energy mechanical system(MEMS) technology can be effectively promoted by the application of field synergy principle and Molecular Dynamics in numerical simulation. Based on this work, the research status of flow, heat transfer and performance improvement in combustion-based MEMS can be presented to relevant researchers more clearly. Highlights: Process in heat transfer performance improvement are summarized. Process in micro combustion performance improvement are summarized. Process in energy conversion performance improvement are summarized. Future works for the performance improvement are introduced.